Role of Basic Education Community School (BECS) in developing Numerical Literacy Skills among Non-formal Learners - Sawar Khan (IJLTP, 2025)
The purpose of this study was to investigate Role of Basic Education Community School (BECS) in developing Numerical Literacy Skills among Non-formal Learners. The researcher used quantitative research design. The population comprised 232 Basic Education Community School (BECS) from Islamabad out of which 5thgraders (42) were purposively selected. The researcher adopted a purposive random sampling technique and collected data by using a self-developed achievement test. Findings indicated that the Basic Education Community School (BECS) played a significant positive role in development of numerical literacy skills among non-formal students. The study recommended that the pattern of education and training provided by BECS may be promoted to other non-formal education providers for the enhancement of unified patterned literacy skills of students.